Exercise Training and Caloric Restriction Prevent Reduction in Cardiac Ca2+-Handling Protein Profile in Obese Rats - Paulino, Ellena Christina; Batista Ferreira, Julio Cesar; Bechara, Luiz Roberto; Tsutsui, Jeane Mike; Mathias, Wilson; Lima, Fabio Bessa; Casarini, Dulce Elena; Cicogna, Antonio Carlos [UNESP]; Brum, Patricia Chakur; Negrao, Carlos Eduardo (Lippincott Williams & Wilkins, 2010)
Previous studies show that exercise training and caloric restriction improve cardiac function in obesity. However, the molecular mechanisms underlying this effect on cardiac function remain unknown. Thus, we studied the effect of exercise training and/or caloric restriction on cardiac function and Ca2+ handling protein expression in obese rats. To accomplish this goal, male rats fed with a high-fat and sucrose diet for 25 weeks were randomly assigned into 4 groups: high-fat and sucrose diet, high-fat and sucrose diet and exercise training, caloric restriction, and exercise training and caloric restriction. An additional lean group was studied. The study was conducted for 10 weeks. Cardiac function was evaluated by echocardiography and Ca2+ handling protein expression by Western blotting. Our results showed that visceral fat mass, circulating leptin, epinephrine, and norepinephrine levels were higher in rats on the high-fat and sucrose diet compared with the lean rats. Cardiac nitrate levels, reduced/oxidized glutathione, left ventricular fractional shortening, and protein expression of phosphorylated Ser(2808)-ryanodine receptor and Thr(17-)phospholamban were lower in rats on the high-fat and sucrose diet compared with lean rats. Exercise training and/or caloric restriction prevented increases in visceral fat mass, circulating leptin, epinephrine, and norepinephrine levels and prevented reduction in cardiac nitrate levels and reduced: oxidized glutathione ratio. Exercise training and/or caloric restriction prevented reduction in left ventricular fractional shortening and in phosphorylation of the Ser(2808)-ryanodine receptor and Thr(17)-phospholamban. These findings show that exercise training and/or caloric restriction prevent cardiac dysfunction in high-fat and sucrose diet rats, which seems to be attributed to decreased circulating neurohormone levels. In addition, this nonpharmacological paradigm prevents a reduction in the Ser(2808)-ryanodine receptor and Thr(17-)phospholamban phosphorylation and redox status. (Hypertension. 2010;56:629-635.)
Keywords: list; obesity; exercise training; caloric restriction; cardiac dysfunction; Ca2+ handling